(untitled) (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article considers the problem of organizing leisure and free time for students, and also suggests a way to improve and optimize the educational process. There is presented the analysis of various views on the modern education system, the problems of youth in the framework of educational activities and the features of the formation of relevant knowledge. Moreover, there are presented the result of a diagnostic study on optimizing the time of summer vacation to influence the level of memorization, motivational sphere and student activity and to ensure the comprehensive development of students in accordance with modern needs.